2018
DOI: 10.1016/j.tiv.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

“Trans-nonachlor increases extracellular free fatty acid accumulation and de novo lipogenesis to produce hepatic steatosis in McArdle-RH7777 cells”

Abstract: Recent studies suggest there may be an environmental exposure component to the development and progression of non-alcoholic fatty liver disease (NAFLD) involving the organochlorine (OC) pesticides or their metabolites. However, the roles of OC compounds in the development of NAFLD has not been fully elucidated. Therefore, the current study was designed to determine if exposure to trans-nonachlor, a prevalent OC compound, could promote hepatocyte lipid accumulation and determine potential pro-steatotic mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Previous studies showed that p,p'-DDE was associated with increases in BMI, triglycerides, insulin resistance, and reductions in HDL cholesterol 7,26 . On the other hand, trans-nonachlor has a pro-steatotic effect on hepatocytes in animal experiments 27 . Unlike oxychlordane, NAFLD did not show a signi cant concentration-dependent association with trans-nonachlor in this study, and further studies are needed to clarify this.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that p,p'-DDE was associated with increases in BMI, triglycerides, insulin resistance, and reductions in HDL cholesterol 7,26 . On the other hand, trans-nonachlor has a pro-steatotic effect on hepatocytes in animal experiments 27 . Unlike oxychlordane, NAFLD did not show a signi cant concentration-dependent association with trans-nonachlor in this study, and further studies are needed to clarify this.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies showed that p,p′ -DDE was associated with increases in BMI, triglycerides, insulin resistance, and reductions in HDL cholesterol 7 , 23 . In addition, trans-nonachlor has a pro-steatotic effect on hepatocytes in animal experiments 24 . Our study suggests that the prevalence of NAFLD may have an independent association with the concentration of OCPs in the general population, some of which showed a linear dose-dependent relationship.…”
Section: Discussionmentioning
confidence: 98%
“…These data are similar to previously published in vitro data indicating exposure to trans-nonachlor has a direct effect on primary rat hepatocytes or rat hepatoma cells to increase either basal or insulin-stimulated de novo lipogenesis with a corresponding increase in insulinstimulated Fasn production in a cell type specific manner. 19,20 While the current animals were fed .5 or 5 ppm of transnonachlor in LFD or HFD for 16 weeks, it is difficult to equate intake with body burden given the bioaccumulative nature of this compound. 18 Therefore, serum levels of trans-nonachlor were determined at the end of the current study to determine body burden and evaluate how the current exposure levels correspond to known human exposure levels (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…These data are similar to previously published in vitro data indicating exposure to trans-nonachlor has a direct effect on primary rat hepatocytes or rat hepatoma cells to increase either basal or insulin-stimulated de novo lipogenesis with a corresponding increase in insulin-stimulated Fasn production in a cell type specific manner. 19,20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation